2011
DOI: 10.1002/wsbm.157
|View full text |Cite
|
Sign up to set email alerts
|

A systems biology approach to synovial joint lubrication in health, injury, and disease

Abstract: The synovial joint contains synovial fluid (SF) within a cavity bounded by articular cartilage and synovium. SF is a viscous fluid that has lubrication, metabolic, and regulatory functions within synovial joints. SF contains lubricant molecules, including proteoglycan-4 and hyaluronan. SF is an ultrafiltrate of plasma with secreted contributions from cell populations lining and within the synovial joint space, including chondrocytes and synoviocytes. Maintenance of normal SF lubricant composition and function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
201
0
24

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(232 citation statements)
references
References 171 publications
7
201
0
24
Order By: Relevance
“…In particular, synovial fluid flow would naturally play a central role in the heat transfer aspect. The performance of human articular joints is indeed strictly connected with the properties of the synovial fluid, which determines load transmission, lubrication, wear inhibition and protection of the articular cartilage from mechanical stresses during joint movements (Bali and Sharma, 2011;Hui et al, 2012). The lubricant properties of synovial fluid are essential in preventing the temperature increase due to friction (Bergmann et al, 2001a(Bergmann et al, , 2001bSawyer et al, 2003;Tandon and Bali, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, synovial fluid flow would naturally play a central role in the heat transfer aspect. The performance of human articular joints is indeed strictly connected with the properties of the synovial fluid, which determines load transmission, lubrication, wear inhibition and protection of the articular cartilage from mechanical stresses during joint movements (Bali and Sharma, 2011;Hui et al, 2012). The lubricant properties of synovial fluid are essential in preventing the temperature increase due to friction (Bergmann et al, 2001a(Bergmann et al, , 2001bSawyer et al, 2003;Tandon and Bali, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Following articular injury, the level of inflammatory cytokines in the synovial fluid increases. Previous studies reported levels of Interleukin 1 and TNF-α to have reached their climax 24 hours after injury (Hui et al, 2012;Lieberthal et al, 2015). These levels remain high for weeks and even months after trauma (Catterall et al, 2010;Olson et al, 2014;Christiansen et al, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…OrthoFlo, MiMedx Group, Inc.). The amniotic fluid contains growth factors, cytokines, proteins, carbohydrates, lipids, hormones, electrolytes, hyaluronic acid as well as other nutrients which play a protective and regulatory role in the inflammatory process and promote regenerative processes [3,40,41]. Although clinical data related to the amniotic fluid is limited, there are studies which indicated that amniotic fluid injections are safe, result in pain reduction and support wound healing [42,43].…”
Section: New Possibilities Of Application Of Grafts Prepared From Plamentioning
confidence: 99%